Imperial nature the World Bank and struggles for social justice in the age of globalization - Goldman, Michael (New Haven Yale University Press, 2005)
Why is the World Bank so successful? How has it gained power even at moments in history when it seemed likely to fall? This pathbreaking book is the first close examination of the inner workings of the Bank, the foundations of its achievements, its propensity for intensifying the problems it intends to cure, and its remarkable ability to tame criticism and extend its own reach.
Includes bibliographical references (p. [317]-343) and index.
Keywords: World Bank